In Vitro Antioxidant, Antityrosinase, and Cytotoxic Activities of Astaxanthin from Shrimp Waste - Sutasinee Chintong; Wipaporn Phatvej; Ubon Rerk-Am; Yaowapha Waiprib; Wanwimol Klaypradit (MDPI AG, 2019)
Astaxanthin is a potent antioxidant compared with vitamins and other antioxidants. However, astaxanthin extract from shrimp processing waste has not yet been used in cosmetic products. This study aimed to explore the natural astaxanthin from shrimp shells for antioxidant and antityrosinase activities as well as potential toxicity. The antioxidant activities were performed with 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging, β-carotene bleaching, and singlet oxygen quenching assays. The results revealed that astaxanthin extract demonstrated potent antioxidant activities against DPPH and ABTS radicals, and prevented the bleaching of β-carotene and quenching of singlet oxygen (EC50 17.5 ± 3.6, 7.7 ± 0.6, 15.1 ± 1.9 and 9.2 ± 0.5 μg/mL, respectively). Furthermore, the astaxanthin extract could inhibit tyrosinase activity (IC50 12.2 ± 1.5 μg/mL) and had no toxic effects on human dermal fibroblast cells. These results suggested that shrimp astaxanthin would be a promising dietary supplement for skin health applications.